Analisis Pengaruh Motivasi terhadap Kepuasan Kerja dan Kinerja Pegawai di PT Sang Hyang Seri (Persero) Regional III Malang - Muslih, Basthoumi (Jurnal Aplikasi Manajemen, 2012)
The purpose of this study is: (1) To determine and analyze the effect of intrinsic and extrinsic motivation on job satisfaction of employees, (2) To determine and analyze the effect of intrinsic and extrinsicmotivation on employee performance, (3) To determine and analyze the effect of job satisfaction on employee performance, (4) To determine and analyze the effect of intrinsic and extrinsic motivation on employeeperformance through employee job satisfaction. This type of research is explanatory research while collecting primary data through distribution of questionnaires to all employees in PT Sang Hyang Seri KR III Malang as many as 40 employees. Sampling technique used is census method. In this case there are two independent variables are analyzed, namely: intrinsic motivation and extrinsic motivation, as well as an intervening variable that is job satisfaction; while the dependent variable is the performance of the employees. The collected data then analyzed by using analysis of PLS (Partial Least Square). The results obtained are (1) Intrinsic and extrinsic motivation has significant effect on job satisfaction, (2) Intrinsic motivation significant direct effect on employee performance, (3) Extrinsic Motivation brings significant effect on theperformance of employees, (4) Job satisfaction has a significant effect on employee performance, (5) intrinsic Motivation causes significant indirect effect on employee performance through job satisfaction, (6) extrinsic Motivation provides significant indirect effect on employee performance through job satisfaction.